The attitude of university students towards the state support of the entrepreneurial ecosystem - Jakubčinová, Martina; Krajčo, Karol; Hotková, Alexandra; Androniceanu, Armenia (Transformations In Business & Economics, 2026)
The aim of this article is to quantify and explore the differences in the attitudes of university students towards the issue of government support for the entrepreneurial ecosystem. Attitudes are examined among students with active entrepreneurial status. The starting point for the fulfilment of the objective was empirical research conducted in Slovakia, the Czech Republic, and Poland (March 2024). The research sample consisted of a total of 1 783 respondents (SK: 576, CZ: 612, and PL: 595) from 42 universities (SK: 16, CZ: 11, and PL: 15). Correlation analysis was used to test and evaluate the formulated hypotheses at the significance level ɑ = 5%. The main results of the research are that the state creates an atmosphere of uncertainty through its business support instruments. Respondents express concern about the quality of the conditions needed to start a business. The financial support for entrepreneurs does not meet the expectations of young people and the administrative burden reinforces the negative impression of entering the business environment. In the context of influencing attitudes, the state will need to pay more attention to the entrepreneurship support area. Minimising the administrative burden can make a significant contribution to growth and competitiveness not only of young entrepreneurs but also of the economy as a whole.